Transcutaneous auricular vagus nerve stimulation may improve cognitive deficits in neuropsychiatric diseases—a systematic review - Jost, Stefanie Theresa; Happe, Fabienne; Koenig, Julian; Dafsari, Haidar S. (Frontiers in Aging Neuroscience, 2026)
BackgroundTranscutaneous auricular vagus nerve stimulation (taVNS) is a safe, effective, and non-invasive therapeutic approach for various neuropsychiatric disorders, including depression, headache disorders, and epilepsy. Cognitive impairment is a common and clinically relevant feature across these conditions, often contributing to poor functional outcomes. While improvements in cognitive performance have been reported in healthy individuals undergoing taVNS, it remains unclear whether taVNS can also alleviate cognitive deficits in individuals with neuropsychiatric disorders.MethodsA comprehensive literature search was performed in PubMed, Embase, and the Cochrane Central Register of Controlled Trials, complemented by manual searches. Predefined inclusion and exclusion criteria were applied. Study selection and data extraction were conducted using the rayyan.ai platform. Reporting followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Synthesis Without Meta-analysis (SWiM) guidelines. The methodological quality of included studies was assessed using the Cochrane Risk-of-Bias tool for randomized trials and the ROBINS-I tool for non-randomized studies. Extracted data included population, intervention, comparator, and clinical outcome variables, as well as stimulation parameters according to the international consensus on vagus nerve stimulation research. Cognitive domains investigated in each study were categorized, and results were summarized using mode statistics and range.ResultsOut of 418 records identified, 146 duplicates were removed. Of the remaining 272 studies, 67 were excluded after title and abstract screening and 192 after full-text assessment. Two additional studies were identified through manual reference screening, resulting in a total of 15 included studies. Eight of these reported improvements in global cognition, attention, memory, language, executive functions or social cognition following taVNS.DiscussionEvidence from the included studies suggests that taVNS may improve cognitive performance in neuropsychiatric disorders. The underlying mechanisms are likely multifactorial, including localized effects within the brainstem and modulation of broader neural networks. Future studies with longer follow-up periods and standardized stimulation protocols are warranted to clarify the cognitive effects of taVNS in neuropsychiatric populations.